A stepwise approach to 'groin pain': a common symptom, an uncommon cause. (16th September 2013) - de Bruijn, Kirstin Marie Jeanne; Franssen, Gaston; van Ginhoven, Tessa Malaika
Abstract : A 70-year-old man was admitted with stinging pain in his right groin radiating towards his inner thigh. In a few days, the pain increased in intensity, he experienced diminished strength in his right leg and got dependent on morphine. Conventional investigations did not show any pathology. A CT-scan revealed a mass in the obturator foramen, indicative of a possible obturator hernia or neuroma of the obturator nerve. However, an additional MRI showed a well-circumscribed cystic mass in the obturator foramen, indicative of a ganglion cyst. This cyst was percutaneously punctured under the CT-guidance and the viscous material was aspirated, after which corticosteroids were injected. After the puncture all symptoms of the patient had completely resolved and the patient was discharged from the hospital without any painkillers.